2018
DOI: 10.1111/jog.13677
|View full text |Cite
|
Sign up to set email alerts
|

Choriocarcinoma with multiple lung metastases from complete hydatidiform mole with coexistent fetus during pregnancy

Abstract: Gestational trophoblastic neoplasm (GTN) is a serious morbidity of complete hydatidiform mole with coexistent fetus (CHMCF) and usually develops after termination of pregnancy. Here we report a case of choriocarcinoma derived from CHMCF during pregnancy. A 33-year-old multiparous woman with suspected CHMCF was admitted with a severe cough. Computed tomography revealed multiple lung metastases. Cesarean section and hysterectomy were performed at 31 weeks of gestation on diagnosis of high-risk GTN from Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…We determined that the CHMCF pregnancy was the source of the choriocarcinoma, which is similar to a case reported by Maeda et al [ 23 ]. Although the patient's prognosis was good with the multidrug combination chemotherapy shown in Table 2 , choriocarcinoma can metastasize to the brain and may have a significant impact on the patient's quality of life and fertility.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We determined that the CHMCF pregnancy was the source of the choriocarcinoma, which is similar to a case reported by Maeda et al [ 23 ]. Although the patient's prognosis was good with the multidrug combination chemotherapy shown in Table 2 , choriocarcinoma can metastasize to the brain and may have a significant impact on the patient's quality of life and fertility.…”
Section: Discussionsupporting
confidence: 88%
“…Sebire et al reported that only four cases of GTN occurring in 77 cases of CHMCF pregnancies (5.2%) required multidrug combination chemotherapy [ 5 ], suggesting CHMCF does not present a high risk for GTN. However, previous case reports describe diagnoses of high-risk GTN after CHMCF or cases requiring multidrug combination chemotherapy for GTN (presumed to be high-risk GTN) [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. In six of 12 cases (50%), including the present case, single-agent chemotherapy was given as the initial chemotherapy for PTD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the patients was 28.7 years, and the mean gestational age at diagnosis was 26.5 weeks. The most common sites of metastases included lungs (89%), brain (39%), vagina (17%), and liver (11%) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…These tumors are characterized by hemorrhage and necrosis, with diffuse staining for cytokeratin 7 and 20. The clinical presentation of metastatic gestational choriocarcinoma to the lung is well described, and more commonly it includes hydatidiform moles (complete or partial), invasive moles, and choriocarcinoma subtypes [2][3][4]. However, spontaneous hemothorax is an uncommon presentation of metastatic gestational choriocarcinoma and has not been reported previously in the United States.…”
Section: Commentmentioning
confidence: 99%